Cone-in-cone structure: New data - I. Kh. Shumilov (Литосфера, 2020)
Research subject. The article presents the results of investigating calcite lenses with a cone-in-cone structure from Middle Devonian clay terrigenous deposits in the Middle Timan.Methods. The investigation of petrographic thin-sections was carried out using a polarizing microscope Nikon eclipse LV100 ND equipped with a Nikon DS Fi2 camera. Polished sections etched with HCl were examined using a scanning electronic microscope JSM-6400 Jeol with a power dispersive spectrometer ISIS Link and a wave spectrometer Microspec. The decomposition of carbonates and the measurement of isotope carbon composition in the mode of continuous helium stream were carried out using a ThermoFisher Scientific analytical complex.Results. It is established that the investigated calcite bodies consists of mosaic block crystals having a drusy structure. Calcite is characterized by abnormally low values S13Ccarb - up to -23.5 %o. Clay films and soapstone inclusions were studied in detail. The formation mechanism of the saw-tooth profile of the upper bound of these inclusions was determined, which consists in the local substitution of alumosilicates with calcite under the maintenance of their relic layered texture.Conclusions. A new version of the crystallization model of carbonate body genesis with a cone-in-cone structure is proposed.